Electrospun aligned poly(ε-caprolactone) nanofiber yarns guiding 3D organization of tendon stem/progenitor cells in tenogenic differentiation and tendon repair - Yang, Qiao; Li, Jianfeng; Su, Weiwei; Yu, Liu; Li, Ting; Wang, Yongdi; Zhang, Kairui; Wu, Yaobin; Wang, Ling (Frontiers in Bioengineering and Biotechnology, 2022)
Hierarchical anisotropy structure directing 3D cellular orientation plays a crucial role in designing tendon tissue engineering scaffolds. Despite the recent development of various fabrication technologies for controlling cellular organization, designing a scaffold mimicking the anisotropic structure of native tendon tissue for improving tenogenic differentiation remains challenging. Herein, we present a list of 3D aligned poly(ε-caprolactone) nanofiber yarns with different diameters fabricated by a dry-wet electrospinning approach, integrating with nano- and micro-scale structure to mimic the hierarchical structure of collagen fascicles and fibers in native tendon tissue. These aligned NFYs exhibited good in vitro biocompatibility, and their ability to induce 3D cellular alignment and elongation of tendon stem/progenitor cells was demonstrated. Significantly, the aligned NFYs with a diameter of 50 µm was able to promote the tenogenic differentiation of tendon stem/progenitor cells due to the integration of aligned nanofibrous structure and the suitable yarn diameter. The rat tendon repair results further showed that bundled NFYs encouraged tendon repair in vivo by inducing neo-collagen organization and orientation. These data suggest that these electrospun bundled NFYs formed by aligned nanofibers can mimic the aligned hierarchical structure of native tendon tissue, which provide potential as a biomimetic multi-scale scaffold for tendon tissue regeneration.